(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of this study was to develop the Verapamil hydrochloride sustained-release floating matrix tablets using gas-generation approach to prolong the gastric residence time. Floating tablets were prepared using hydroxypropyl methylcellulose K4M (HPMC) as hydrophilic gel material, sodium bicarbonate as gas-generating agent and Citric Acid as floating assistant agent. A 32 factorial design was used to select the optimized formulation wherein HPMC K4M (X1) and Citric Acid (X2) were taken as independent variables and Floating lag time (FLT), amount of drug release after 24hrs. (Q24) were taken as dependent variables. The release data were evaluated by the model-dependent (curve fitting) method using PCP Disso v2.08 software. Optimisation studies were carried out by using the Design Expert software (version 8.0.1). The floating tablets were evaluated for uniformity of weight, hardness, thickness, swelling index, friability, drug content, FLT, and in vitro release. The in vitro drug release followed Hixson-Crowell model and mechanism of drug release was found to be anomalous or non-fickian type. The optimized formulation was F3 containing HPMC K4M 15%, and Citric acid 3% having minimum FLT and maximum drug release after 24 hrs.